A Study of an Industrialization Strategy for China's Upper-Middle Income Stage. (3rd July 2019) - Qunhui, Huang; Yanghua, Huang; Jun, He
Abstract : When the high-income East Asian economies entered the upper-middle income stage, their long-term growth was sustained by their real manufacturing output share and total factor productivity (TFP). This is a typical pattern that is highly consistent with classical development economics, which sees manufacturing as the engine of economic growth. When China became a middle-income country, its share of real manufacturing output and TFP both fell over the same period, exhibiting a theoretical and empirical tendency toward "premature deindustrialization" that increases the risk of being caught in the middle-income trap. Accelerating China's development as a manufacturing power, advancing high-tech manufacturing and improving the quality and efficiency of traditional industries are realistic options for the country's industrial development strategy.